Compliance and Understanding Of Village Treasurers Compliance Regarding Tax Obligations in The Village Of Kota Pari, North Sumatrra - Yunita Sari Rioni; Dwi Saraswati; Roro Rian Agustin (CERED Indonesia Institute, 2025)
Tax compliance and understanding are very important because in order to make proper tax payments, one must have a thorough understanding of human resources. One of the areas that must be improved is calculation, with tax reports being prepared by the village treasurer. The village treasurer is responsible for managing village funds, including calculation, deduction, and tax reporting. If you are not aware of this, it will cause serious problems for government financial reports. Previous research on taxation and understanding has been conducted. Researchers want to study this at the village treasurer's office. Kota Pari Village analyzed whether the CIP burden is a village. Understand your responsibilities when reporting taxes. The study used an explanatory method with a qualitative approach. This study is based on the results of interviews with village officials. This tax compliance and understanding of the CIP burden. I am responsible for the tax report. Aspects of compliance and taxes and taxes, basic tax rules are followed, understood, calculated and deducted in accordance with taxes. CIPUSE is very good at doing its job. But there are several obstacles to the implementation of tax reporting.